MICROBIAL PATTERN AND ANTIBIOTIC SUSCEPTIBILITY IN PEDIATRIC INTENSIVE CARE UNIT DR. SOETOMO HOSPITAL, SURABAYA - A.A.W., I Wayan Putra; Irwanto, Irwanto; Dharmawati, ira; Setyaningtyas, Arina; Puspitasari, Dwiyanti; Wahyu, Agung Dwi; Kuntaman, Kuntaman (Institute of Topical Disease Universitas Airlangga, 2019)
Gram-negative bacterial are known as common pathogen caused infection in Pediatric Intensive Care Unit (PICU). Microbial Pattern and Antibiotic Susceptibility are needed as clinical data for selected appropriate antibiotic therapy. In PICU Dr. Soetomo hospital until now still lacking of Microbial Pattern and Antibiotic Susceptibility data. This descriptive study is to recognized Microbial Pattern and Antibiotic Susceptibility in PICU patients from blood, urine, sputum, stool, cerebrospinal fluid, endotracheal tube, pus swab and pleural fluid culture specimens. Patients whose admitted into PICU without signs of infections were excluded from the study. The inclusion criteria are patients with sign infection as follows: fever < 36,5°C or > 37.5°C, leukocyte < 4000/mm3 or > 10000/mm3, marker infections CRP >10 mg/L or PCT >0,3 ng/mL, bradycardia or tachycardia, tachypnea, infiltrates on chest X-ray, turbid urine, dysuria, thrombophlebitis, abdominal pain or tenderness, and mucous or skin lesion. Medical record data from 2011 to 2016, revealed 1138 patients had positive microbial culture result, wherein positive result came from blood 44.46%, urine 19.15%, sputum 11.59%, stool 8.96%, cerebrospinal fluid 7.50%, endotracheal tube 4.04%, pus swab 2.89%, and pleural fluid 1.41%. The microorganisms found in PICU Dr. Soetomo was dominated with gram negative bacteria. Commonest bacterial that recognized from blood was B. cepacea, urine was E. coli, sputum was P. aeruginosa, Stool was E. coli, Cerebrospinal fluid was S. cohnii, endotracheal tube was K. pneumoniae ESBL, pus swab was S. aureus, and pleural fluid was S. maltophilia. Both gram-negative bacteria and gram-positive bacteria isolates revealed multiple drug resistance to commonly used antibiotic, but still had good susceptibility for antibiotic such as; amikacin, cefoperazone-sulbactam, linezolid, vancomycin and carbapenem group.